PENGEMBANGAN MEDIA GAMBAR REALITA DALAM PEMBELAJARAN IPS DI SD - Apriliyani Apriliyani; Sudjarwo Sudjarwo; Pargito Pargito (Jurnal Studi Sosial / Journal of Social Studies, 2014)
The aims of development research are to produce picture media product to social science learning at natural, artificial feature and dividing time in Indonesia. Other aim is to find out the effectiveness of result development product usage at social science learning. This approach is research and development. Test result shown that reality picture media get good scoring by learning expert, and good scoring by learning media expert. At small group test shown good response but media layout is still clear enough. At field test, media result scoring shown good response, and the effectiveness of media usage appear from correlation of between student response and media through study achievement significantly. The conclusion is that the result picture media development is suitable to be use in social science learning at fifth grade of elementary school and effectiveness tested using correlation test contingency, contingency coefficient C count is greater than the value of the product moment (0.6490.349). Tujuan penelitian ini adalah menghasilkan produk berupa media gambar realita untuk pembelajaran IPS pada materi kenampakan alam, buatan serta pembagian waktu di Indonesia dan untuk mengetahui efektifitas penggunaan produk hasil pengembangan media tersebut. Pendekatan yang digunakan adalah penelitian dan pengembangan. Hasil uji coba memperoleh penilaian cukup baik oleh ahli pembelajaran dan ahli media. Sedang uji coba kelompok kecil menunjukkan respon yang baik dan uji coba lapangan menunjukkan respon lebih baik dan  efektif. Kesimpulanya adalah hasil penilaian ahli materi, ahli media dan siswa dinyatakan layak digunakan dan hasil uji coba produk dinyatakan efektif yang diuji dengan kolerasi kontingensi diperoleh koefisien kontingensi C hitung lebih besar dari nilai produk moment (0,6490,349).Kata kunci: gambar realita, media, pembelajaran ips, pengembangan